Taxonomic notes on †Clidicostigus arachnipes Jałoszyński, Brunke & Bai, 2017, a predominant ant-like stone beetle in the mid-Cretaceous Burmese amber - Cao, Hai-Jing; Liu, Yu-Wei; Liu, Hao-Yu (Zootaxa, 2025)
The fossil species Clidicostigus arachnipes Jałoszyński, Brunke & Bai, 2017 is a predominant ant-like stone beetle from the mid-Cretaceous Burmese amber. With the discovery of additional materials, it exhibits greater variation in the morphological characters such as body size and coloration, as well as relative lengths of antennomeres and maxillary palpomeres, which are summarized in the present study. In addition, some characters in protibiae, labial palpi and elytra are illustrated.